Effect of polishing and bleaching on color, whiteness, and translucency of CAD/CAM monolithic materials - Peña, Ranulfo Castillo [UNESP]; Ramos, Alejandro Cardenas [UNESP]; dos Santos Nunes Reis, José Maurício [UNESP]; Dovigo, Lívia Nordi [UNESP]; Salomon, Jean-Pierre Guy Olivier; del Mar Pérez, María; Fonseca, Renata Garcia [UNESP] (Wiley, 2024)
Objective: To evaluate the effect of polishing and bleaching on the recovery of lightness, color, whiteness, and relative translucency parameter (RTP) in CAD/CAM materials and changes in these properties when another staining in coffee was conducted after the treatments. Materials and Methods: Disks of Lava Ultimate (LU), Vita Enamic (VE), IPS Empress CAD (EMP), IPS e.max CAD (EMAX), and Vita Suprinity (VS) were (1) not treated (control), (2) polished with Proxyt or (3) Ceramisté, (4) bleached with Opalescence PF or (5) Whiteness HP Blue, and (6) air polished with Clinpro Prophy Powder. CIE L*a*b* color coordinates were registered at baseline (R0), after staining with coffee for 30 min daily for 36.5 days and treatment (R1), and after another staining (R2). Differences (R1–R0 and R2–R0) in lightness (ΔL00), color (ΔE00), RTP (ΔRTP00), and whiteness (ΔWID) were evaluated by mixed repeated measures ANOVA and 95% confidence intervals (α = 0.05) and interpreted in function of their respective 50:50% PT and AT thresholds. Topography was evaluated by scanning electron microscopy (SEM). Results: In LU, Opalescence PF and Proxyt decreased (Formula presented.), (Formula presented.), and (Formula presented.) and showed lower (Formula presented.), (Formula presented.), and (Formula presented.). In VE, all treatments decreased (Formula presented.), (Formula presented.), and (Formula presented.), whereas (Formula presented.), (Formula presented.), and (Formula presented.) were lower in Opalescence PF than in the control group. In both moments, ΔE00 and ΔWID in EMP (also ΔL00) and EMAX were higher in Opalescence PF than in the control group, from which the other treatments did not differ in R1–R0. In EMP, (Formula presented.) in Whiteness HP Blue (also (Formula presented.)) and Proxyt were also higher in comparison to the control group and in VS, Ceramisté decreased (Formula presented.), (Formula presented.), and (Formula presented.), whereas Opalescence PF increased (Formula presented.). (Formula presented.) of Ceramisté and (Formula presented.) and (Formula presented.) of Proxyt were lower than those of the control group. Conclusions: The most suitable treatment to recover the lightness, color, whiteness, and RTP without changing these properties after another coffee exposure is material-dependent. Clinical Significance: Although the effectiveness of the treatment was material-dependent, Proxyt was the only treatment that promoted clinically acceptable changes for both LU and VE, while for purely ceramic materials, this condition was observed with Ceramisté and Clinpro Prophy Powder.
Keywords: bleaching; CAD/CAM materials; color; lightness; polishing; translucency; whiteness